2022
DOI: 10.1155/2022/1247806
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Kallikrein Protects Rat Prostate against the Inflammatory Damage in a Chronic Autoimmune Prostatitis Model via Restoring Endothelial Function in a Bradykinin Receptor B2-Dependent Way

Abstract: Objective. The aim of this study was to investigate whether tissue kallikrein (KLK1) can protect the prostate from inflammatory damage and the mechanism involved in it. Methods. A total of 50 male Wistar rats were used in this study. Initially, 20 rats were sacrificed to obtain the prostate antigen to induce experimental autoimmune prostatitis (EAP), and the remaining 30 rats were randomly divided into 5 experimental groups (normal control group (NC group), NC+KLK1 group (NCK group), EAP group, EAP+KLK1 group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Nakamura (37) et al who indicated to the About 54% of BPH patients avoided biopsy based on PSA/hk2 results. Studies did not refer to the evaluation of the level of hk2 in patients with prostatitis, but that Zhang (39) et al In an experimental study, they indicated that the level of kallikrein is lower in mice with prostatitis compared to mice with BPH. As for the FGG level, Table (1) shows that the mean ± standard deviation of the FGG level was (2138.21 ± 283.629) ng/ml in patients of the G1 group and (1277.084 ± 259.377)ng/ml in patients in the G2 group and (2323.452 ± 487.541) ng/ml in patients of the G3 group, and (796.616 ± 403.845) ng/ml in the healthy group as a control group.…”
Section: Resultsmentioning
confidence: 99%
“…Nakamura (37) et al who indicated to the About 54% of BPH patients avoided biopsy based on PSA/hk2 results. Studies did not refer to the evaluation of the level of hk2 in patients with prostatitis, but that Zhang (39) et al In an experimental study, they indicated that the level of kallikrein is lower in mice with prostatitis compared to mice with BPH. As for the FGG level, Table (1) shows that the mean ± standard deviation of the FGG level was (2138.21 ± 283.629) ng/ml in patients of the G1 group and (1277.084 ± 259.377)ng/ml in patients in the G2 group and (2323.452 ± 487.541) ng/ml in patients of the G3 group, and (796.616 ± 403.845) ng/ml in the healthy group as a control group.…”
Section: Resultsmentioning
confidence: 99%
“…Iron chelator DFO and free radical scavenger EDA prevent ferroptosis by reducing iron availability and lipid peroxidation. 9 Journal of Immunology Research [17]. In the current study, the EAP model was developed in the similar method.…”
Section: Discussionmentioning
confidence: 99%
“…The long disease course, poor efficacy and heavy disease burden have seriously affected the quality of life of male patients worldwide [3]. BPH is a complex inflammatory disease, and a study has shown that inflammation plays a key role in the etiology of BPH [4]. Periodontitis is a chronic inflammatory disease, caused by destructive dental pathogens, has become a worldwide challenge [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%